The music shop : [large type] a novel - Joyce, Rachel (Random House Large Print, 2018)
"It is 1988. On a dead-end street in a run-down suburb there is a music shop that stands small and brightly lit, jam-packed with records of every kind. Like a beacon, the shop attracts the lonely, the sleepless, and the adrift; Frank, the shop's owner, has a way of connecting his customers with just the piece of music they need. Then, one day, into his shop comes a beautiful young woman, Ilse Brauchmann, who asks Frank to teach her about music. Terrified of real closeness, Frank feels compelled to turn and run, yet he is drawn to this strangely still, mysterious woman with eyes as black as vinyl. But Ilse is not what she seems, and Frank has old wounds that threaten to reopen, as well as a past it seems he will never leave behind. Can a man who is so in tune with other people's needs be so incapable of connecting with the one person who might save him?"--Page 4 of cover.